URVASHI O JOHNNY: A POIGNANT LAMENT FOR THE MARGINALIZED AND A CALL FOR CHANGE IN MAHASWETA DEVI'S DRAMATIC VISION - Patteti, Raja Sekhar; Rao, Songa Srinivasa (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Mahasweta Devi’s Urvashi O Johnny (1976) is a powerful exploration of romantic idealism, social ethics, and existential despair against the backdrop of urban poverty in Calcutta. The play follows Johnny, a ventriloquist whose passion for Urvashi symbolizes his quest for personal and collective freedom in a world crippled by systemic oppression. Johnny’s relentless pursuit of happiness, his guilt over abandoning One-Eyed Moti, and his ultimate sacrifice mirror the struggles of the marginalized in a society defined by greed and moral decay. Employing poetic language, folk songs, and raw dialects, Devi critiques the suppression of dissent and the dehumanization of the underprivileged, while celebrating their resilience and compassion. The play is both a lamentation of lost voices and a call to action, exposing the fractures of modern civilization and challenging the audience to rethink their role in perpetuating inequities.